Wearing the niqab: Muslim women in the UK and the US - Piela, Anna (Dress cultures, 2021)
Erasing niqabi women's voices: mainstream media representations -- Reclaiming niqabi voices: mainstream and social media -- Religious framing of the niqab -- Translating the niqab for secular audiences -- Intersections of Islamophobia, racism and sexism and coping strategies